Physiological functions of protein kinase D in vivo. Issue 2 (3rd January 2013) - Ellwanger, Kornelia; Hausser, Angelika
Abstract The cellular functions of the serine/threonine protein kinase D (PKD) have been extensively studied within the last decade and distinct roles such as fission of vesicles at the Golgi compartment, coordination of cell migration and invasion, and regulation of gene transcription have been correlated with this kinase family. Here, we highlight the current state of in vivo studies on PKD function with a focus on animal models and discuss the molecular basis of the observed phenotypic characteristics associated with this kinase family. © 2013 IUBMB Life, 65(2)98–107, 2013